Evaluation of a school‐based transition program designed to facilitate school reentry following a mental health crisis or psychiatric hospitalization. Issue 8 (23rd June 2017) - White, Henry; LaFleur, Jennifer; Houle, Katherine; Hyry‐Dermith, Paul; Blake, Susan M.
Abstract: In recent decades, increasing attention has been paid to the number of adolescents experiencing extended absences from school due to mental health crises. Upon returning to school, these students often face difficulties in functioning, risk of relapse, and vulnerability to academic failure and social isolation. This paper presents results of a study examining a school‐based support program model designed to provide short‐term academic, social, and emotional support to help students successfully reacclimatize to school after an extended absence. The paper describes demographic, academic, and clinical characteristics of 189 program participants across eight high schools. Improvements were observed in participants' day‐to‐day functioning based on the results of pre/postassessments completed by program clinicians. Preliminary data showed positive trends in participants' school attendance and high school graduation rates. Finally, the paper considers implications for school‐based mental health practice and next steps in related research.